2010
DOI: 10.4028/www.scientific.net/amr.152-153.1734
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Scaffold from Recombinant Spider Silk Protein in Tissue Engineering

Abstract: As a new biomaterial, recombinant spider silk protein has attracted much attention in tissue engineering. The pNSR-16/ BL21(DE3)pLysS strains fermented and produced the recombinant spider silk protein, which was then cast into scaffolds. NIH-3T3 cells were cultivated with extractions of the scaffolds in vitro. The cytotoxicity of scaffolds was analyzed with a MTT assay. The performances of cells adhesion, growth and expression on the scaffolds were observed with SEM, HE staining and immunohistochemistry. Compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…The facilitation of endothelial cell growth was further demonstrated on pNSR16/Gt‐PU composite nanofibers, in agreement with previous studies using fibroblasts and endothelial . This was definited because gelatin and spider silk protein were both biocompatible materials being gift of cellular signal site, which can promote cell proliferation.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The facilitation of endothelial cell growth was further demonstrated on pNSR16/Gt‐PU composite nanofibers, in agreement with previous studies using fibroblasts and endothelial . This was definited because gelatin and spider silk protein were both biocompatible materials being gift of cellular signal site, which can promote cell proliferation.…”
Section: Resultssupporting
confidence: 90%
“…Not only spider silk but also recombinant spider silk proteins are attracting more and more attention due to their potential mechanical property and perfect biocompatibility . Likewise, added with cell signaling amino acid sequence arginine‐glycin‐aspartic acid (RGD), a recombinant spider silk protein named pNSR16 has been successfully applied in small‐diameter vascular tissue engineering by our laboratory and finally identified its role in improving cell adhesion and proliferation . Compared with another natural protein, apart from common biological origin and biodegradability, gelatin (Gt) will make up for the hydrophobic defects of pNSR16 by virtue of its hydrophilic amino acids .…”
Section: Introductionmentioning
confidence: 99%
“…Foams remain one of the most ideal classes of material as they exhibit a high strength-to-weight ratio. Many research groups have demonstrated the use of recombinantly produced spidroins to manufacture highly porous and interconnected foam-like structures, used for example as 3D cell culture scaffolds. Wang et al fabricated porous foams from a recombinantly produced spider silk protein called pNSR-16 containing the RGD motif cell-binding domain . The authors made the foams by dissolving the proteins with formic acid followed by the addition of NaCl.…”
Section: Bioengineering Of Protein-based Materialsmentioning
confidence: 99%
“…Wang et al [58] reported production of porous foams made of the recombinant spider silk protein pNSR-16. This recombinant spider silk protein also comprises an RGD motif.…”
Section: Porous Foamsmentioning
confidence: 99%